PERAN PENGETAHUAAN KEUANGAN, GAYA HIDUP HEDONISME, KONTROL DIRI,DAN LITERASI KEUANGAN DALAM MANAJEMEN KEUANGAN PRIBADI GENERASI Z DI KABUPATEN SUMBAWA - Sherwin Ary Busman; Hartini Hartini; Agus Santoso (Politeknik Bisnis Indonesia, 2022)
The purpose of this study was to analyze the effect of financial knowledge, hedonism lifestyle, self-control and financial literacy on the personal financial management of the z generation in Sumbawa Regency. The method used with quantitative methods and data collection techniques using a questionnaire. The sample in this study amounted to 100 respondents obtained by purposive sampling technique with the criteria of people living in Sumbawa and aged 24-44 years. Data analysis in this study used Partial Least Square (PLS) with Smart PLS. The results of this study indicate that 1) Financial Knowledge has a significant effect on Personal Financial Management 2) Hedonism Lifestyle has a significant effect on personal financial management 3) Self-Control has a significant effect on personal financial management 4) Financial Literacy has a significant effect on personal financial management.